Test of Different Effectiveness of Candirejo Tourist Village Cooperative Asset Management - Ottavia, Niendi Devie; Setiawan, Mulyo Budi (Jurnal Ekonomi, 2024)
This research aims to examine differences in asset management variables consisting of asset management effectiveness, asset grouping effectiveness, and asset use effectiveness in the Candirejo Tourism Village Cooperative before and after implementing digitalization of asset management through the Information and Asset System (SiASET) in the Candirejo Tourism Village Cooperative. This type of quantitative research originates from qualitative data which is converted into numbers or scored. This research explains the relationship between differences between variables. This research used a sample of 10 respondents from members of the Candirejo Tourism Village Cooperative through an interview system. Through the Paired Sample T-Test Dependent Test stage using Excel software as a supporting tool in data analysis. The results of the research show that there are differences between asset management variables consisting of asset management effectiveness, asset grouping effectiveness, and effective use of assets of the Candirejo Tourism Village Cooperative, before and after implementing digitalization of asset management through the Information and Asset System (SiASET) in the Tourism Village Cooperative Candirejo.